A note on cascading failures in communication networks and power grids - Gomes, Teresa (2020)
An overview of recent works regarding the main aspects of cascading failures in interdependent power grids and communication networks, is presented. Modelling approaches to cascading failures propagation and strategies to mitigate the impact of those cascading effects are discussed. The identification of critical elements and robust design against cascading failures are also reviewed. Finally some concluding remarks regarding the need for a more realistic representation of the interaction between both networks are put forward.